2011
DOI: 10.1111/j.1365-2559.2011.04043.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour budding and other prognostic pathological features at invasive margins in serrated colorectal adenocarcinoma: a comparative study with conventional carcinoma

Abstract: Compared to CC, SAC displayed more HG-TB, HG-CyPs and fewer PLI at the invasive margins and this may account for its poorer clinical outcome. TB, CyPs, TGP and PLI are useful histological prognostic aids in SAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 43 publications
4
41
0
Order By: Relevance
“…We have previously reported a different histological phenotype in SAC [16] and have confirmed the higher incidence of TB in this tumor type. Here we have studied the immunophenotype shown in the CT and at the IF, particularly in TB and non-TB aggregates, in a wellcharacterized series of SACs.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…We have previously reported a different histological phenotype in SAC [16] and have confirmed the higher incidence of TB in this tumor type. Here we have studied the immunophenotype shown in the CT and at the IF, particularly in TB and non-TB aggregates, in a wellcharacterized series of SACs.…”
Section: Discussionsupporting
confidence: 74%
“…Population, salient clinicopathological features, and follow-up information of patients with CRC included in this study have been previously reported [15,16]. The histological criteria for the diagnosis of SAC include epithelial serrations, clear or eosinophilic cytoplasm, abundant cytoplasm, vesicular nuclei, absence of or less than 10% necrosis of the total surface area, mucin production, and cell balls and papillary rods in mucinous areas of a tumor [17].…”
Section: Patients and Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This process resembling epithelial-mesenchymal transition does usually not occur in serrated carcinomas of the CIMP-H/BRAF/MSI-H type. By contrast, in other carcinomas from the serrated pathway such as those showing CIMP-H/BRAF/MSS [7,14,89,90] tumor budding is frequently observed.…”
Section: Role Of Braf In Colon Cancermentioning
confidence: 77%